Toughen and harden metallic glass through designing statistical heterogeneity. (1st March 2016) - Wang, Yongwei; Li, Mo; Xu, Jinwu
Abstract: Although having remarkable mechanical properties, metallic glass is severely limited by the lack of toughness and hardening ability which are among the basic requirements for structural and functional applications. Various attempts have been made experimentally to address these issues but with very limited improvement. Here we report a new attempt via material design approach using finite element modeling. We deliberately introduce statistical heterogeneity into the metallic glass samples, i.e. free volume dispersity. We show that the plasticity and toughness can be enhanced systematically with the increase of the heterogeneity and in certain circumstance even apparent hardening can be achieved. We will discuss the underlying mechanisms and also possible design of new metallic glass composites using the concept of heterogeneity dispersion. Graphical abstract: The local strain and free volume distribution in a metallic glass undergoing tension at 10% strain in brittle ((a) and (b)) and ductile ((c) and (d)) samples.